2022
DOI: 10.1590/fst.106021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and survey of nutrition and sensory quality in domestic and foreign milk sold in China

Abstract: Consumer choice of milk commonly lacks a scientific basis, and consumers are often unable to obtain the most suitable milk for themselves. As far as know, data profile has not been used to investigate and compare the quality of domestic and foreign milk in Chinese market. Therefore in the current study, we compared the quality of 112 domestic brands and 48 foreign brands using independent samples t-test, correlation analysis, multivariate linear regression analysis, principal component analysis and sensory ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…A panel of 10 healthy individuals trained in milk evaluation was recruited. The panellists' requirements, as outlined in the literature (Cai et al ., 2022), were as follows: (i) five males and five females; (ii) aged 20–25; (iii) good health and no lactose intolerance; (iv) possess adequate language and textual expression abilities to accurately and properly convey evaluation results; (v) abstain from using strong cosmetics or perfume that would affect taste score; (vi) no smoking within 1 h prior to evaluation; (vii) abstain from eating hot pot, garlic, onion or other strongly flavoured foods within 1 h prior to evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of 10 healthy individuals trained in milk evaluation was recruited. The panellists' requirements, as outlined in the literature (Cai et al ., 2022), were as follows: (i) five males and five females; (ii) aged 20–25; (iii) good health and no lactose intolerance; (iv) possess adequate language and textual expression abilities to accurately and properly convey evaluation results; (v) abstain from using strong cosmetics or perfume that would affect taste score; (vi) no smoking within 1 h prior to evaluation; (vii) abstain from eating hot pot, garlic, onion or other strongly flavoured foods within 1 h prior to evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…To maintain the quality and meet the transportation requirements, there are three types of processed milk being produced: ultra‐high temperature sterilised (UHT) milk, pasteurised milk and formula milk powder. Among the three, pasteurised milk is believed to be the most nutritious (Cai et al ., 2022) since it can retain its bioactive components, such as immunoglobulin, lactoferrin, lactalbumin and lactoglobulin, which can promote human immune system (Donovan, 2016; Bakar et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory analysis is a common method to evaluate food quality (Cai et al, 2022;Hu et al, 2022;Lopes et al, 2021;Zhang et al, 2021). The sensory evaluation of eggs was performed in the sensory analysis laboratory in Jimei University with the temperature of 22 °C and humidity of 60%.…”
Section: Sensory Analysismentioning
confidence: 99%
“…However, recently, many well-known milk powder enterprises were found that the "vanillin" flavor in the milk powder seriously exceeded the standard, and a special medical milk powder called "betamethasone" came out. These milk powders have serious potential food safety hazards (Li et al, 2021;Cai et al, 2022). Some consumers think that improvements of the law and increased attention to food safety by government can improve the quality of domestic milk (Cai et al, 2022).A range of factors affect the quality of milk, including the variety of cow, type of feed and rearing environment (Santiago et al, 2019;Cai et al, 2022;Santos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These milk powders have serious potential food safety hazards (Li et al, 2021;Cai et al, 2022). Some consumers think that improvements of the law and increased attention to food safety by government can improve the quality of domestic milk (Cai et al, 2022).A range of factors affect the quality of milk, including the variety of cow, type of feed and rearing environment (Santiago et al, 2019;Cai et al, 2022;Santos et al, 2022). Detection of residues of feed additives and toxic substances in milk, such as veterinary drugs, bacteria and heavy metals, was important for controlling the quality of milk (Rabelo et al, 2021;Cai et al, 2022;Karaman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%